Functioning of the Adenine Nucleotide Transporter in the Arsenate Uncoupling of Corn Mitochondria - Bertagnolli, B. L. (1973)
Arsenate uncouples mitochondrial respiration in a process stimulated by ADP, inhibited by oligomycin, and competitively inhibited by inorganic phosphate. If mersalyl is added to corn mitochondria to block further transport of accumulated arsenate, the uncoupled respiration continues unabated due to recycling of matrix arsenate. Addition of ADP now inhibits rather than promotes respiration and the mitochondria shrink. It is established by arsenate analyses that arsenate is removed from the matrix. Oligomycin or atractyloside block the removal by inhibiting ADP-arsenate formation or transport, respectively. It is deduced that ADP-arsenate is stable in the membrane and is transported outward for hydrolysis in the external aqueous phase. Hence, ADP-arsenate formed in oxidative phosphorylation is not directly released to the matrix, and a mechanism must exist for its direct transfer to the transporter.